Effects on Mechanical and Physical Properties of Ta Element Addition to Ti-6Al-7Nb Alloy - Caligulu, Ugur; Durmus, Hulya; Kejanli, Haluk; Keskinkilic, Ali Riza; Balci, Esra (Springer, 2025)
Ti and its alloys play a leading role in biomedical applications within the field of materials science. In this study, different amounts of Ta were added to the TiAlNb alloy. Various analyses were carried out to determine the physical and chemical properties of the produced samples. DSC (differential scanning calorimetry), and XRD (X-ray diffraction) analyses were conducted to determine the phase transformations and crystal structure of the alloys, respectively. SEM-EDX (scanning electron microscopy) and OM (optical microscopy) images were taken to analyze the chemical structure of the samples and to examine their microstructures in more detail. Microhardness and wear resistance tests were performed to determine some mechanical properties of the produced samples. It was observed that increasing the tantalum content increased both hardness and wear resistance. These findings suggest that the addition of tantalum to the Ti-6Al-7Nb alloy could be an effective strategy to improve biomaterial performance.
Keywords: Martensitic-Transformation; Ti-Al; Antibacterial Properties; Phase-Transformation; Thermal-Properties; Substituting Nb; Temperature; Microstructure; Behavior